Economic Growth in European Union NUTS-3 Regions - Kilroy, Austin; Ganau, Roberto (World Bank, Washington, DC, 2020)
This paper analyzes the growth pathways of 1,321 regions in the European Union from 2003 to 2017. The aim is to inform integrated territorial investments and other economic development initiatives in lagging regions. Using the definition of lagging regions from the European Commission’s Catching Up Initiative, more than two-thirds of the European Union member states have lagging regions when defined at the Nomenclature of Territorial Units for Statistics-3 scale. These small lagging regions are often hidden within larger and more prosperous regions. The paper considers the roles of industrial structure, innovation, and inward foreign direct investment as growth-enhancing factors. The findings indicate that the growth dynamics in low-income regions are different from those in regions in other income groups: there is no overall pattern in the contribution of industry to growth but there is a strong association between foreign direct investment and growth. Among low-growth lagging regions -- the 171 small regions in the European Union with gross domestic product per capita less than 90 percent of the European Union average, and stagnant or negative growth performance -- growth is correlated with construction and innovation. There are also differences in the growth pathways of rural and non-rural regions: growth is associated with moving away from agriculture in rural regions, and it is associated with construction and innovation in non-rural regions. The results imply that a finer geographic scale can be important in policy making and programming of Cohesion Policy Funds, to cater to different needs and opportunities at the scale of Nomenclature of Territorial Units for Statistics-3 regions.